Analysis of Digital Technology-Based Visual Arts Learning at Cahaya Khalifah Islamic Elementary School - Ni Nyoman Shinta Anggriani; Andi Imrah Dewi; Kadek Hariana; Zulnuraini Zulnuraini; Andi Rahmaeni (Edu Cendikia: Jurnal Ilmiah Kependidikan, 2026)
This study aimed to analyze the implementation of digital technology-based fine arts learning in developing the creativity of sixth-grade students at Cahaya Khalifah Islamic Elementary School. The research used a qualitative method with a case study approach involving one teacher and 20 students as participants. Data were collected through observation, interviews, and documentation, then analyzed using the Miles and Huberman interactive analysis model, including data reduction, data display, and conclusion drawing. The findings showed that digital technology-based fine arts learning was implemented through three stages: introduction, core activities, and closing activities. In the learning process, teachers acted as facilitators who guided students in utilizing various digital platforms such as Canva, Pinterest, Google Images, WhatsApp, and artificial intelligence applications to create visual artworks. The integration of digital technology encouraged students to explore ideas more freely and creatively. Students’ creativity developed in four dimensions: fluency, flexibility, originality, and elaboration. Furthermore, the use of digital media increased students’ motivation, participation, confidence, and engagement during learning activities. Students became more active in expressing artistic ideas, collaborating with peers, and producing innovative visual artworks. The study concludes that digital technology-based fine arts learning effectively supports the development of students’ creativity and provides broader opportunities for artistic exploration through innovative and interactive digital media in elementary school learning.